2005
DOI: 10.4050/1.3092852
|View full text |Cite
|
Sign up to set email alerts
|

Water Impact Test and Simulation of a Composite Energy Absorbing Fuselage Section

Abstract: In March 2002, a 25-ftls vertical drop test of a composite fuselage section was conducted onto water. The purpose of the test was to obtain experimental data characterizing the structural response of the fuselage section during water impact for comparison with two previous drop tests that were performed onto a rigid surface and soft soil. For the drop test, the fuselage section was configured with ten 100-lb. lead masses, five per side, that were attached to seat rails mounted to the floor. The fuselage sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…A similar fuselage section with an integrated crushable foam subfloor concept and simulated payload was used in previous studies involving vertical drop tests on various impact surfaces [7,8]. Sareen et al [7] studied the response of the fuselage section during a 25-fps vertical drop on a hard surface and soft soil (sand) and Fasanella et al [8] reported on the response of the same fuselage section during a 25-fps vertical drop on water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar fuselage section with an integrated crushable foam subfloor concept and simulated payload was used in previous studies involving vertical drop tests on various impact surfaces [7,8]. Sareen et al [7] studied the response of the fuselage section during a 25-fps vertical drop on a hard surface and soft soil (sand) and Fasanella et al [8] reported on the response of the same fuselage section during a 25-fps vertical drop on water.…”
Section: Discussionmentioning
confidence: 99%
“…Sareen et al [7] studied the response of the fuselage section during a 25-fps vertical drop on a hard surface and soft soil (sand) and Fasanella et al [8] reported on the response of the same fuselage section during a 25-fps vertical drop on water. Therefore, a loose comparison of the two concepts can be made for corresponding impact surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens do not collapse after maximum loading is achieved and exhibit a complex unloading response. The composite fuselage section was developed during a three-year research program in the late 1990's and has since been used as a test bed to evaluate structural scaling effects, multi-terrain impacts, seat and occupant loadings, and model correlation studies [22][23][24][25][26][27][28][29][30][31]. A pre-test photograph of the test article is shown in Figure 21 …”
Section: Three-point Bend: Test/analysis Correlationmentioning
confidence: 99%
“…A lot of research was conducted with respect to composite sine wave beams in the subfloor structure that are crushed under vertical crash loads [4][5][6][7][8][9]. Further concepts are based on foam [10] or honeycomb absorbers [11,12] in the subfloor structure. Illustration of aircraft fuselage drop test for crashworthiness evaluation.…”
Section: Introductionmentioning
confidence: 99%